The economics of innocent fraud: truth for our time - Galbraith, John Kenneth (Houghton Mifflin, 2004)
Introduction and personal note --The nature of innocent fraud -- The renaming of the system -- The economics of accommodation -- The specious world of work -- The corporation as bureaucracy -- The corporate power -- The myth of the two sectors -- The world of finance -- The elegant escape from reality -- The end to corporate innocence -- Foreign and military policy -- The last word